Changes in Pulmonary Microenvironment Aids Lung Metastasis of Breast Cancer - Wu, Meimei; Liang, Yanfang; Zhang, Xin (Frontiers in Oncology, 2022)
Breast cancer has become the most common malignant disease in the world according to the International Agency for Research on Cancer (IARC), and the most critical cause of death is distant metastasis. The lung is the extremely common visceral site for breast cancer metastasis. Lung metastasis of breast cancer is not only dependent on the invasive ability of the tumor itself, but also closely relates to the pulmonary microenvironment. In the progression of breast cancer, the formation of specific microenvironment in lungs can provide suitable conditions for the metastasis of breast cancer. Pulmonary inflammatory response, angiogenesis, extracellular matrix remodeling, some chemotherapeutic agents and so on all play important roles in the formation of the pulmonary microenvironment. This review highlights recent findings regarding the alterations of pulmonary microenvironment in lung metastasis of breast cancer, with a focus on various cells and acellular components.